The Moderating Effect of Management Control Systems on the Strategy-Performance Relationship in Indonesian Construction Companies - Zaitul Zaitul; Desi Ilona; Elfiswandi Elfiswandi (UPI YPTK Journal of Business and Economics, 2016)
This study is aimed to explore the effect of Management Control System (MCS) on the relationship betweenbusiness strategy and construction company performance. Most of prior studies on business strategy andmanagement control system interaction have been done using non-construction companies. This study usesseventy three (73) construction companies in Padang city (Indonesia). The data is gathered through surveyusing questionaire. Moderated Regression Analysis (MRA) is employed using SPSS software. Furthermore,this paper finds that when management control system include in the model, there is an increasing in modelfeasibility and power. However, management control system does not play as moderating variable betweenbusiness strategy and construction company performance. This finding is inconsistent to prior studiesconcluding that management control system strengthens the relationship between strategy and performance.